STRUCTURE OF THE INFORMATION COMPETENCE OF FUTURE TEACHERS OF ENGINEERS SEWING PROFILE (Journal of Information Technologies in Education (ITE), 2012)
In the article the component structure of information competency of future engineers and educators, which builds on the personal, cognitive, operational activity-related, reflexive and evaluative components.
Keywords: an engineer and teacher; information competence; the components of the formation of information competence